Evaluation of clinical success and marginal adaptations of inlay and onlay restorations manufactured after conventional and digital impressions: a prospective randomized controlled clinical study - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2021)
Aim: The aim of the present study was to compare inlay and onlay restorations fabricated from conventional impressions and two different digital impression systems in terms of clinical features and marginal fit. Materials and methods: Participants were randomly assigned to three groups according to the type of impression system used. The impressions were taken with polyvinyl siloxane silicone material for the control group (CON). For the digital impressions, Trios Pod Scanner (3Shape) was used for the TRIOS group and Cerec AC Omnicam (Sirona) for the CEREC group. A total of 40 IPS e.max CAD and 20 IPS e.max Press (both Ivoclar Vivadent) inlay and onlay restorations were then placed in 24 participants. Clinical evaluations, Plaque Index, Gingival Index, and pocket probing depth measurements were taken at baseline, 6 months, and 12 months using FDI criteria. The continuous margin percentages were quantitatively examined by scanning electron microscopy at baseline and 12 months. Results: All the restorations showed clinically acceptable measurements at baseline, 6 months, and 12 months. The continuous margin evaluations showed no statistically significant difference between the groups. Conclusions: Based on the 12-month follow-up results, inlay and onlay restorations fabricated with digital impressions were found to be a reliable alternative to conventional impressions.
Keywords: Trios; Cerec; clinical follow-up; in vivo marginal adaptation; randomized controlled clinical trial; PARTIAL CERAMIC CROWNS; POSTERIOR TEETH; SURVIVAL RATE; PERFORMANCE; CEMENTS; PLAQUE; RESIN